Life Satisfaction, Ethnicity and Neighbourhoods: Is There an Effect of Neighbourhood Ethnic Composition on Life Satisfaction? - Lucinda Platt; Gundi Knies; Alita Nandi (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
Using a rich, nationally representative data set with a large sample of minorities and matched small area characteristics, we explore differences in life satisfaction for ethnic groups living in UK. We test the hypothesis that minorities will be less satisfied, which will in part be explained by less favourable individual and area contexts, but that living in areas with a larger proportion of own ethnic group promotes well-being. We find that satisfaction is lower among minorities, ceteris paribus, but area concentration is associated with higher life satisfaction for certain groups. We discuss the implications of our findings.
Keywords: I31; J15; R23; O15; 330; Life Satisfaction; Happiness; Ethnic group; Neighbourhood; Subjective well-being; UKHLS